Familial chylomicronemia: A rare case report (Indian Journal of Case Reports, 2020)
We report a 5-day-old neonate born out of 3rd-degree consanguinity who presented with milky blood, hepatosplenomegaly, and lipemia retinalis (fundus examination). The baby was asymptomatic, euglycemic, and did not have xanthomas. Lipid profile was altered (total cholesterol - 2340 mg/dl, triglycerides (TG) - >10,000 mg/dl, high-density lipoprotein - <5 mg/dl, lipoprotein (a) - <10.1 mg/dl, and apolipoprotein A1 - 795 mg/dl). Lipid profile of mother, father, and elder sibling were normal. The baby was started on skimmed milk powder and medium-chain TGs powder. The baby is under follow-up and lipid profile is improving.